Optimization of molding parameter effect to warpage and shrinkage based on plastic flow simulation software: handphone casing - Mohd Norhafizi, Rohaizat (2010)
Injection molding is a manufacturing process for producing part for both thermoplastic and thermosetting plastic material. Objective of this project to determine the parameter effect to the warpage and shrinkage of the handphone casing and to determine the optimization parameter for reduce the warpage and shrinkage. For this project 3D scanner are use to scan the hand phone casing to get the parameter and analyse with MoldFlow simulation software to optimize the effect to warpage and shrinkage. Shrinkage and warpage tendencies in molded parts,are influenced by actions taken in each and all of the manufacturing stages of part design, material selection, tool design, and processing. The mold temperature(MT), packing time (Pt), packing pressure (PP) and cooling time (Ct) in the packing stage are considered as machining parameters. As increase in mold temperature (MT), the shrinkage also increase and as increase in cooling time (Ct), the shrinkage decrease. Other than that, as increase the packing pressure (PP), the shrinkage usually decrease.